2013
DOI: 10.1080/03601277.2013.802184
|View full text |Cite
|
Sign up to set email alerts
|

Attracting and Training Tomorrow's Gerontologists: What Drives Student Interest in Aging?

Abstract: Demographic and labor force trends point to a critical need for professionals trained to work with older adults. The current study investigated factors associated with interest in aging-related topics and careers and knowledge of the opportunities that exist in the field of gerontology. Descriptive statistics, Pearson correlation analysis, and multiple regression analyses were used to examine results of a survey of 300 college students representing a wide range of disciplines. Aging-related coursework and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 29 publications
1
24
0
4
Order By: Relevance
“…Three hundred students studying gerontology, physical and occupational therapy, health policy, psychology, speech language pathology, and non-healthrelated courses were surveyed. 3 Aging coursework, experiential learning, and frequency and quality of formal contact were positive predictors, whereas aging anxiety and ageism were significant negative predictors of interest in working with older adults. Similar results were found in graduate students in a social work program, with rewarding interactions with older adults, contact frequency, and self-rated geriatric skill level predicting pursuit of aging-related employment.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Three hundred students studying gerontology, physical and occupational therapy, health policy, psychology, speech language pathology, and non-healthrelated courses were surveyed. 3 Aging coursework, experiential learning, and frequency and quality of formal contact were positive predictors, whereas aging anxiety and ageism were significant negative predictors of interest in working with older adults. Similar results were found in graduate students in a social work program, with rewarding interactions with older adults, contact frequency, and self-rated geriatric skill level predicting pursuit of aging-related employment.…”
mentioning
confidence: 89%
“…Predictors of interest in working with older adults have been explored in college and medical school students. Three hundred students studying gerontology, physical and occupational therapy, health policy, psychology, speech language pathology, and non‐health‐related courses were surveyed . Aging coursework, experiential learning, and frequency and quality of formal contact were positive predictors, whereas aging anxiety and ageism were significant negative predictors of interest in working with older adults.…”
mentioning
confidence: 99%
“…Plusieurs auteurs se sont consacrés à l'analyse des causalités associées à cette faible orientation vers les cursus et les professions du vieillir (Bergman, Erickson, & Simons, 2014 ;Chippendale & Boltz, 2015 ;Chonody, 2015). À ce titre, Kastenbaum (1964), dans ses travaux précurseurs, a observé que peu de clinicien.ne.s avaient, à cette époque, bénéficié d'une formation ad hoc.…”
Section: La Prégnance De L'âgisme Sur Les Choix De Carrière Et Les Prunclassified
“…La majorité des auteurs traitant de la problématique à l'étude s'accordent, ensuite, sur l'influence négative de l'âgisme sur le parcours scolaire et professionnel des étudiant.e.s (Adam, 2016 ;Archambault, 2006 ;Bergman et al, 2014 ;Chippendale & Boltz, 2015 ;Chonody, 2015 ;Dobbin, 2012 ;Dumbrell et al, 2007 ;Gaymard, 2006 ;Gutheil, Heyman, & Chernesky, 2009 ;Haight, Christ, & Dias, 2008 ;Masse & Meire, 2012 ;Méthot, 2006 ;Moreau, Laki, & Kilik, 2009 ;Snyder, Wesley, Lin, & Lay, 2008). Ainsi, depuis plusieurs années, l'âgisme représente la forme de discrimination la plus prégnante au sein de nos sociétés hypermodernes, et ce, malgré la probabilité accrue, pour tout un chacun, d'appartenir un jour à la catégorie décriée (Champvert, 2014).…”
unclassified
“…Even recently published systematic literature reviews, such as that of Liu et al (2012) and Wang and Chonody (2013), have found that results of the studies on attitudes towards older people were inconsistent, with positive, negative and neutral attitudes being noted across various groups of health care professionals. Bergman et al (2014) investigated factors associated with interest in aging-related topics and careers and knowledge about the opportunities that exist in the field of gerontology. Their study includes a survey of 300 college students representing a wide range of disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%